Cooperative Sensing Scheme for Acquisition of Rotational Synchronization of Radar - Lee, Juhyung; Baek, Hoki; Lim, Jaesung (IEEE Systems Journal, 2020)
Recently, radar frequency bands have been considered as promising candidates for cognitive radio (CR) owing to their low utilization. From a temporal access perspective, a substantial number of spectral opportunities could be exploited if CR users could achieve rotational synchronization with radar. However, to the best of our knowledge, no research has been focused on this synchronization issue. In this article, we propose a rotational synchronization scheme between radar and CR networks to opportunistically access the radar band. First, we propose a framed structure with sensing and transmission phases reflecting the rotational characteristics of radar. Second, we provide a cooperative synchronization algorithm. To determine the appropriate spectrum sensing timing in the proposed frame, we use a statistical approach via maximum a posteriori estimation considering the sensing abilities of CR users. We analyze the synchronization error of our proposed scheme via simulations.
Keywords: Cooperative sensing; Maximum a posteriori estimation; Radar frequencies; Sensing abilities; Statistical approach; Synchronization algorithm; Synchronization error; Synchronization scheme; Cognitive radio (CR); cooperative systems; radar; radar detection; radar tracking